2011
DOI: 10.1007/s11357-011-9235-3
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of age-related changes in FOXO3a activity and the PI3K/Akt pathway by short-term feeding of ferulate

Abstract: Ferulate (4-hydroxy-3-methoxycinnamic acid) is a well-known phenolic compound that scavenges free radicals and exerts anti-inflammatory effects. Forkhead box O3a (FOXO3a), a transcription factor that plays important roles in aging processes, decreases with age and is negatively regulated through phosphorylation by phosphatidylinositol 3-kinase (PI3K)/Akt signaling. The present study investigated the efficacy of short-term ferulate feeding on age-related changes in PI3K/Akt/FOXO3a and upstream insulin signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…Western blotting was performed as described previously [12]. Homogenized samples were boiled for 5 min in gel-loading buffer (125 mM Tris-HCl, 4% SDS, 10% 2-mercaptoethanol, pH 6.8, and 0.2% bromophenol blue) at a 1:1 ratio.…”
Section: Western Blottingmentioning
confidence: 99%
“…Western blotting was performed as described previously [12]. Homogenized samples were boiled for 5 min in gel-loading buffer (125 mM Tris-HCl, 4% SDS, 10% 2-mercaptoethanol, pH 6.8, and 0.2% bromophenol blue) at a 1:1 ratio.…”
Section: Western Blottingmentioning
confidence: 99%
“…The phosphorylation of FoxO3a by Akt leads to its association with 14-3-3 proteins and subsequent nuclear exclusion, retention, and degradation in the cytoplasm, which deactivates the FoxO3a pathway [1,2]. Conversely, the inhibition of Akt phosphorylation, which results in the dephosphorylation, nuclear translocation, and activation of FoxO3a, leads to the expression of target genes associated with aging [3], apoptosis [4], oxidative stress [5], and cell cycle progression [6]. Thus, this protein exhibits different functions based on cell type.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, oxidative stress is considered a major factor contributing to the aging process and leads to aberrant signaling pathways. Aged rats have increased oxidative stress and weakened antioxidative defense systems [3]. Therefore, it is necessary to attenuate oxidative stress and strengthen the antioxidant system to modulate altered signaling pathway molecules to constrain the aging process.…”
Section: Introductionmentioning
confidence: 99%
“…In pregnancy, trophoblast cells always circulate in the blood circulation throughout mother's body, hence an immunological reaction between trophoblast cells and immune system occurs in mother's body. Under these conditions, the shorter the time of the pregnancy interval, mother's immunologic reaction disorder will more likely increase, thus increasing the incidence of hydatidiform mole pregnancy in mother with high parity [19].…”
Section: ) Correlation Between Age and Parity And Pakt Immunoexpressionmentioning
confidence: 99%
“…The expression of Akt itself increases with age. Choi et al [19] showed that ferulate administration in rats can suppress Akt activity, and thus inhibit the aging process.…”
Section: ) Correlation Between Age and Parity And Pakt Immunoexpressionmentioning
confidence: 99%